Cyberbullying and Its Relationship to Social Isolation:A Field Study on a Sample of Students at the Faculty of Arts, Misurata University (Al-Farooq Journal of Sciences, 2026)
This study aimed to explore the relationship between the manifestations of cyberbullying and the tendency toward social isolation among students of the Faculty of Arts at Misurata University. The study adopted a descriptive-correlational research design, targeting a population of 908 male and female students, from which a simple random sample of 136 students was selected. Data collection utilized the Cyberbullying Scale developed by Omnya Ibrahim El-Shennawy (2014), alongside a social isolation questionnaire designed by the researcher.The results revealed a statistically significant positive correlation between all aspects of cyberbullying and the tendency toward social isolation. It was observed that mockery and defamation, digital exclusion, harassment and privacy violation, insult and cyberthreats, and cyber-sexual harassment are all associated with an increased level of social isolation among students.
Keywords: Cyberbullying, Social Isolation, University Students, Misurata University.